Promoter Interference in a Bacteriophage Lambda Control Region: Effects of a Range of Interpromoter Distances - Strainic, Michael G. (American Society for Microbiology, 2000)
The p(R) and p(RM) promoters of bacteriophage lambda direct transcription in divergent directions from start sites separated by 83 phosphodiester bonds. We had previously shown that the presence of an RNA polymerase at p(R) interfered with open complex formation at p(RM) and that this effect was alleviated by the deletion of 10 bp between the two promoters. Here we present a detailed characterization of the dependence of the interference on the interpromoter distance. It was found that the reduced interference between the two promoters is unique to the 10-bp deletion. The relief of interference was demonstrated to be due to the facilitation of a step subsequent to RNA polymerase binding to the p(RM) promoter. A model to explain these observations is proposed. A search of known Escherichia coli promoters identified three pairs of divergent promoters with similar separations to those investigated here.